2011
DOI: 10.1002/cjoc.201180280
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Determination of Quercetin and Myricetin from Chamaecyparis obtusa by Ionic Liquids‐based Monolithic Cartridge

Abstract: A short ionic liquids (ILs)-based monolithic cartridge was prepared and used as the selective extraction sorbent. After the material was evaluated by field emission-scanning electron microscopy (FE-SEM), a new approach for the extraction and determination of quercetin and myricetin from Chamaecyparis obtusa (C. obtusa) by using ILs-based, monolithic cartridge system was developed. Chromatographic analysis was conducted on a C 18 column with UV detection at 372 nm, an eluting solution consisting of acetonitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…ILs are salts composed of cations and anions and are liquids at ambient temperatures []. In recent years, there has been increasing interest in ILs as novel solvents for synthesis, separation, electrochemistry, and process chemistry because of their unique properties that make them useful in a range of areas in modern chemistry []. Wang et al [] explored a room temperature, ILs‐mediated nonhydrolytic sol–gel protocol for fabrication of new molecularly imprinted HSMs.…”
Section: Hsm Materialsmentioning
confidence: 99%
“…ILs are salts composed of cations and anions and are liquids at ambient temperatures []. In recent years, there has been increasing interest in ILs as novel solvents for synthesis, separation, electrochemistry, and process chemistry because of their unique properties that make them useful in a range of areas in modern chemistry []. Wang et al [] explored a room temperature, ILs‐mediated nonhydrolytic sol–gel protocol for fabrication of new molecularly imprinted HSMs.…”
Section: Hsm Materialsmentioning
confidence: 99%
“…[12,13] On the other hand, the methods for purifying the target compounds from the solvent extract require improvement. Solid-phase extraction (SPE) is the most widely used target-substrate pretreatment of complicated matrices, [14,15] with ongoing research focused on finding suitable SPE materials for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…About the quantification of QCT, some recent and relevant reports include the exploitation of a graphite oxide and ionic liquid modified electrode (Jiuji et al, 2013), or the use of Ag nanoparticles/1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl) imide based β-cyclodextrin/epichlorhydrin composite electrode (Franzoi et al, 2010). On the other hand, the exploitation of ionic liquids (ILs) for the extraction of phenolic compounds from herbal products (Liu et al, 2014) and medicinal plants (Xu et al, 2012;Bogel-Lukasik et al, 2010a;Zhu et al, 2011) has been demonstrated during the past few years. In fact, ILs can create various types of interactions with substrates and organic compounds, hydrogen bonds, van der Waals, dipole-dipole, dispersive and electrostatic forces being the most common of these interactions (Bogel-Lukasik et al, 2010a;Bogel-Lukasik et al, 2010b;Bogel-Lukasik et al, 2010c;Domanska & Bogel-Lukasik, 2005).…”
Section: Introductionmentioning
confidence: 99%